VIBROACOUSTIC SIGNALS IN CUTTING METALS - Fayzimatov Bakhodir Numanovich; Khusanov Yunusali Yuldashalievich; Abduvoxidov Shaxriyor Zikrullo o‘g‘li (International Engineering Journal For Research & Development, 2021)
This article provides information on the analysis of the process of generation of vibroacoustic signals during cutting.